Abravanel's theory of prophecy, with special reference to his commentary on Deuteronomy 18:9-22 - Malherbe, Johannes Stefanus (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1993.